Introduction to real analysis - Bartle, Robert G.; Sherbert, Donald R.; Bartle, Robert G. (New York, John Wiley Sons, Inc, 2000)
In recent years, mathematics has become valuable in many areas, including economics and management science as well as the physical sciences, engineering and computer science. Therefore, this book provides the fundamental concepts and techniques of real analysis for readers in all of these areas. It helps one develop the ability to think deductively, analyze mathematical situations and extend ideas to a new context. Like the first two editions, this edition maintains the same spirit and user--friendly approach with some streamlined arguments, a few new examples, rearranged topics, and a new chapter on the Generalized Riemann Integral.
Appendix A-E, 334-356p.; Bibliographical references 357p.; Index 381-388p.
Keywords: Real variables; Mathematics